2005
DOI: 10.1007/s00330-005-2864-0
|View full text |Cite
|
Sign up to set email alerts
|

Variants of the superior labrum and labro-bicipital complex: a comparative study of shoulder specimens using MR arthrography, multi-slice CT arthrography and anatomical dissection

Abstract: The purpose of the present study was to evaluate the anatomical variability of the superior labrum and to compare the value of MR arthrography and multi-slice CT arthrography in the diagnosis of variants of the labro-bicipital complex. Forty-three human shoulder specimens (age range and mean age at death, 61-89 years and 78.3 years) were examined with the use of MR arthrography and multi-slice CT arthrography prior to joint exploration and macroscopic inspection of the superior labrum and labro-bicipital compl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
69
0
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 87 publications
(71 citation statements)
references
References 18 publications
1
69
0
1
Order By: Relevance
“…In this instance, the labrobicipital complex has been described as loosely attached to the glenoid rim in a fashion analogous to the lateral meniscus in the knee. There have been varying depths of medial extension of the cleft observed (Smith et al, 1996;Waldt et al, 2006). The incidence of this anatomical variation may be more common than previously thought (Smith et al, 1996;Kreitner et al, 1998;Waldt et al, 2006).…”
Section: Introductionmentioning
confidence: 72%
See 4 more Smart Citations
“…In this instance, the labrobicipital complex has been described as loosely attached to the glenoid rim in a fashion analogous to the lateral meniscus in the knee. There have been varying depths of medial extension of the cleft observed (Smith et al, 1996;Waldt et al, 2006). The incidence of this anatomical variation may be more common than previously thought (Smith et al, 1996;Kreitner et al, 1998;Waldt et al, 2006).…”
Section: Introductionmentioning
confidence: 72%
“…There have been varying depths of medial extension of the cleft observed (Smith et al, 1996;Waldt et al, 2006). The incidence of this anatomical variation may be more common than previously thought (Smith et al, 1996;Kreitner et al, 1998;Waldt et al, 2006). In a cadaveric study in which CT arthrogram and MR imaging were compared with macroscopic dissection of the labrobicipital complex, Waldt et al (2006) observed significant variability in the attachment of the superior labrum to the glenoid and a sublabral recess in 74% of cases.…”
Section: Introductionmentioning
confidence: 80%
See 3 more Smart Citations